2019
DOI: 10.1186/s13287-019-1444-1
|View full text |Cite
|
Sign up to set email alerts
|

The factors present in regenerating muscles impact bone marrow-derived mesenchymal stromal/stem cell fusion with myoblasts

Abstract: BackgroundSatellite cells, a population of unipotent stem cells attached to muscle fibers, determine the excellent regenerative capability of injured skeletal muscles. Myogenic potential is also exhibited by other cell populations, which exist in the skeletal muscles or come from other niches. Mesenchymal stromal/stem cells inhabiting the bone marrow do not spontaneously differentiate into muscle cells, but there is some evidence that they are capable to follow the myogenic program and/or fuse with myoblasts.M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 87 publications
0
13
0
Order By: Relevance
“…The migration ability of these cells was improved by both IL-4 and SDF-1, but none of these factors increased the ADSCs' potential to fuse with mouse C2C12 myoblasts. It was previously shown that MSCs from bone marrow and Wharton's jelly are able to interact with myoblasts and form hybrid myotubes and that SDF-1 or IL-4 improve this process [50,51,55,68]. We also showed that human cells, e.g., those isolated from connective tissue of umbilical cord or bone marrow-derived mesenchymal cells, can form hybrid myotubes with mouse myoblasts [51,68].…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…The migration ability of these cells was improved by both IL-4 and SDF-1, but none of these factors increased the ADSCs' potential to fuse with mouse C2C12 myoblasts. It was previously shown that MSCs from bone marrow and Wharton's jelly are able to interact with myoblasts and form hybrid myotubes and that SDF-1 or IL-4 improve this process [50,51,55,68]. We also showed that human cells, e.g., those isolated from connective tissue of umbilical cord or bone marrow-derived mesenchymal cells, can form hybrid myotubes with mouse myoblasts [51,68].…”
Section: Discussionmentioning
confidence: 53%
“…It was previously shown that MSCs from bone marrow and Wharton's jelly are able to interact with myoblasts and form hybrid myotubes and that SDF-1 or IL-4 improve this process [50,51,55,68]. We also showed that human cells, e.g., those isolated from connective tissue of umbilical cord or bone marrow-derived mesenchymal cells, can form hybrid myotubes with mouse myoblasts [51,68]. Interestingly, SDF-1 which was shown by us to increase CD9 expression in mouse MSCs [50,58], did not have such an impact on rat ADSCs.…”
Section: Discussionmentioning
confidence: 99%
“…As we mentioned above, bone marrow-derived MSCs do not present naïve myogenic potential (45). These cells do not fuse in the absence of myoblasts and rarely fuse with myoblasts in co-cultures (45,(50)(51)(52)(53). However, bone marrow-derived MSCs could follow myogenic differentiation as the result of reprogramming induced by 5-azacytidine treatment, overexpression of Notch intracellular domain (NICD), paired box transcription factor 3 (Pax3), or constitutively active β-catenin, or as a result of 3D co-culture with myofibers (54)(55)(56)(57)(58)(59).…”
Section: Introductionmentioning
confidence: 95%
“…MSCs do not possess myogenic differentiation capacity, but they are able to fuse to myoblasts to a small extent [54]. Differentiation capacity can be induced by the overexpression of Pax3 or β-catenin and by the satellite cell niche, but not by the niche's factors IGF-1, IL-4, IL-6 or SDF-1 [55][56][57][58]. Additionally, MSCs showed a positive effect on muscle regeneration in Duchenne muscular dystrophy model mice by secreting the chemokine CXCL12 and osteopontin [59].…”
Section: Mscs In Muscle Diseasesmentioning
confidence: 99%